Influenza vaccine uptake in Tunisia from two high-risk groups’ perception and attitudes: a qualitative study - Boukthir, Aicha; Bouguerra, Hind; Ben Salah, Afif; Erber, Astrid C.; Chaabene, Sana; Moussa, Hayet; Guillemette, François; Alaya, Nissaf Ben; Bettaieb, Jihene (Frontiers in Public Health, 2023)
Background: Pregnant women (PW) and elderly with chronic diseases (ECD) are priority groups for the influenza vaccination. This study was designed to have a better insight into the influenza perceptions and barriers of the vaccine uptake from these groups' perspectives.Methods: This qualitative study consisted of 20 focus group discussions (FGDs) enrolled from five governorates across the country (north, center, and south) between March 18 and July 10, 2019, in urban and rural areas. FGDs were conducted in Arabic (Tunisian dialect) and following the topic guide. Data were transcribed in the local language then translated into English and analyzed using Nvivo12 Software. This permitted the analysis thematic approach, using codes determined by the focus groups.Results: A total of 170 individuals participated in the FGDs (84 ECD and 86 PW). Both groups recognized the weakness of the immune system as key determinant for severity. While PW raised the lack of information about the vaccine, the ECD emphasized accessibility problems. Five main barriers to influenza vaccination were identified: cultural barriers and use of traditional medicine, misleading or lack of information about influenza and the vaccine, advice against its uptake, problems of availability and accessibility of the vaccine as well as mistrust towards the vaccine including adverse effects, vaccine composition and effectiveness.The study provided refined information from the perspectives of users to orient the policies regarding the promotion of influenza vaccine by decision makers among these two high risk groups.